1989
DOI: 10.1037/0022-3514.57.1.136
|View full text |Cite
|
Sign up to set email alerts
|

Life events, fitness, hardiness, and health: A simultaneous analysis of proposed stress-resistance effects.

Abstract: The effects of exercise participation, self-perceived fitness level, and dispositional hardiness for promoting stress resistance were examined in a sample of 373 college students. Self-report measures of stressful life experience and recent physical illness were positively correlated, and fitness and hardiness were negatively correlated with illness as expected. Multiple regression analyses indicated that neither fitness nor hardiness provided a stress-moderator effect because neither was found to significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 31 publications
5
69
2
Order By: Relevance
“…Studies with a variety of occupational groups have found that hardiness operates as a significant moderator or buffer of stress (e.g., Bartone, 1989;Contrada, 1989;Kobasa, Maddi, & Kahn, 1982;Roth, Wiebe, Fillingim, & Shay, 1989;Wiebe, 1991). Hardiness has also been identified as a moderator of combat exposure stress in Gulf War soldiers (Bartone, 1993(Bartone, , 1999a(Bartone, , 2000.…”
Section: Personality Hardinessmentioning
confidence: 99%
“…Studies with a variety of occupational groups have found that hardiness operates as a significant moderator or buffer of stress (e.g., Bartone, 1989;Contrada, 1989;Kobasa, Maddi, & Kahn, 1982;Roth, Wiebe, Fillingim, & Shay, 1989;Wiebe, 1991). Hardiness has also been identified as a moderator of combat exposure stress in Gulf War soldiers (Bartone, 1993(Bartone, , 1999a(Bartone, , 2000.…”
Section: Personality Hardinessmentioning
confidence: 99%
“…Stressful life experiences have been shown to directly correlate with increased illness 8 , and recent research has shown a dramatic increase in the levels of stress experienced by college students over the past thirty years 9 . In response to these increasing levels of stress, students often engage in negative health behaviors (e.g., drinking, smoking).…”
Section: Coping Tacticsmentioning
confidence: 99%
“…Research studies with a variety of occupational groups have found that hardiness functions as a significant moderator or buffer in the stress-health relation (Kobasa, Maddi & Puccetti 1982;Roth, 1989;Collins, 1991;J. L. Blgbee, 1992;Williams et al, 1992;Bartone, 1998).…”
Section: Methodsmentioning
confidence: 99%